Tongo in Segou, Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Tongo village's first well, which the women say is still fast and very serviceable. Photos taken from the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) research benchmark site in Tongo, Segou in Mali.